2009
DOI: 10.1038/ismej.2008.128
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between N-cycling communities and ecosystem functioning in a 50-year-old fertilization experiment

Abstract: The relative importance of size and composition of microbial communities in ecosystem functioning is poorly understood. Here, we investigated how community composition and size of selected functional guilds in the nitrogen cycle correlated with agroecosystem functioning, which was defined as microbial process rates, total crop yield and nitrogen content in the crop. Soil was sampled from a 50-year fertilizer trial and the treatments comprised unfertilized bare fallow, unfertilized with crop, and plots with cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
300
7
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 495 publications
(356 citation statements)
references
References 30 publications
39
300
7
10
Order By: Relevance
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
“…The abundance of nosZ gene was the highest one among the three functional genes in this study. This result was higher than those of previously reported: nosZ density of 3×10 6 -2.8×10 8 copies g −1 dry soil (Kandeler et al 2006;Dandie et al 2008;Hallin et al 2009). But Chronakova et al (2009) found the nosZ gene copy number was in a range of 9.1×10 7 -7.5×10 9 copies g −1 soil in an upland pasture soil.…”
Section: Abundances Of Nirs Nirk and Nosz Genes Under Different Irrcontrasting
confidence: 73%
“…Previous studies showed that denitrification enzyme activity was correlated with the copy numbers of nirK gene (Throbäck et al, 2007) and nosZ gene (Hallin et al, 2009), suggesting that denitrifiers harboring these functional genes played an important role in the denitrification process, and the abundance of the denitrifying community could predict the corresponding process (Hallin et al, 2009). The mean EC 50 values of pyrene for copy numbers of nirK, nirS and nosZ genes were lower than that of pyrene for PDA, indicating that denitrifiers harboring nirK, nirS or nosZ gene was more sensitive to pyrene than PDA, and denitrifiers harboring nirS gene was more sensitive to pyrene than that harboring nirK or nosZ gene.…”
Section: Abundance Of the Denitrifying Communitymentioning
confidence: 99%
“…The activity of reductases and the expression of functional genes involved in denitrification process varies among individual strains (Zumft, 1997), and community composition is thus considered to be able to influence functionality at both community and ecosystem levels (Braker et al, 2010). Nevertheless, some studies have reported correlations between abundance and function as well as between structure and function of denitrifying communities (Bremer et al, 2009;Hallin et al, 2009;Rich et al, 2003) while others not Miller et al, 2008;Wertz et al, 2009). Therefore, it is important to determine the correlations among changes in function, abundance and composition of the denitrifying community in an agricultural soil in response to PAHs stress.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in three forest ecosystems indicated that shifts of soil C/N ratio, soil acidification, and root exudation reduction induced by N saturation caused bacterial biomass decreasing under long-term fertilization (Wallenstein et al 2006). Nitrogen fertilization has previously been shown to increase the abundance of soil AOB, which dominated N-rich environments (Di et al 2009;Hallin et al 2009). However, we observed an insignificant effect of fertilization on AOB and AOA abundance (see Fig.…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 99%
“…1b). A 50-year-old fertilization experiment showed that amoA gene copy numbers of AOB and AOA under several fertilized treatments were insignificant, except for the ammonium sulfate treatment (Hallin et al 2009). That difference may be explained by the fact that the application of ammonium sulfate would lower the soil pH value.…”
Section: Responses Of Aob and Aoa Abundance To Soil Warming And Fertimentioning
confidence: 99%